An Experimental Study of Concentrator Photovoltaic Thermoelectric Generator with Different Concentrator Positions Using Real-Time IoT Monitoring - Khadijah Ramli; Sahari, Norain (Progress in Engineering Application and Technology, 2024)
In response to the growing demand for efficient and sustainable energy solutions, this project investigates a novel way to addressing issues in renewable energy generation. A Concentrated Hybrid Photovoltaic-Thermoelectric (CPV-TE) system with integrated Internet of Things (IoT) monitoring is introduced in the project. However, maintaining the elevated working temperature of CPV cells is a significant concern because it can reduce the system’s lifetime and power conversion efficiency. To overcome this issue, combining a CPV system with TEG provides a hybrid design that efficiently harnesses both electrical and thermal outputs, maximising solar energy utilisation and recovering wasted heat from the solar panel. The fundamental goal of the project is to create a CPV-TE system that can harvest energy from sunshine and temperature changes. The system attempts to improve solar energy conversion efficiency by using the benefits of concentrated photovoltaic (CPV) technology and thermoelectric (TE) energy harvesting. To enable real-time data monitoring, IoT technologies, notably ThingSpeak, are integrated. The experiment requires adjusting the distance between the Fresnel lens and the solar panel to match the focal length. The experiment runs for four days, gathering data from 11 a.m. to 4 p.m., and examines four scenarios, each with a different Fresnel lens position. The results provide subtle insight into the effect of Fresnel lens location on solar panel performance. While a 16.5 cm spacing appeared to be promising for maximising immediate output, extended-duration performance revealed that other factors were at work. Overall, the Fresnel lens boosted voltage and power outputs, highlighting the difficulty of optimising solar energy systems. Finally, the study accomplishes its goals by offering a complete investigation into the CPV-TE system dynamics. The CPV-TE system, which incorporates IoT for real-time monitoring, is an effective option for renewable energy harvesting. The findings emphasise the need of taking into account elements such as solar coverage, temperature dynamics, and complementary technologies for optimal and long-term performancE